A fast x-ray photoelectron spectroscopy study of the adsorption and temperature-dependent decomposition of propene on Ni(100) - Whelan, Caroline; Neubauer, Ralf; Borgmann, Dieter; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Chemical Physics, 2001)
Propene uptake at 105 was experimentally studied. A single molecular adsorption state was observed. Changes in methyl group peak binding energy revealed adsorbate-adsorbate interactions and a dispersed phase growth mechanism. A notable result is the observation that a new surface species evolves above 200 K from decomposition of di-σ-bonded propene.